Pulsed pressure pickling enhances acetic acid transfer, thiosulfinates degradation, color and ultrastructure changes of "Laba" garlic. (October 2020) - Zhang, Yang; Zielinska, Magdalena; Vidyarthi, Sriram K.; Zhao, Jin-Hong; Pei, Yu-Peng; Li, Gaofei; Zheng, Zhi-An; Wu, Min; Gao, Zhen-Jiang; Xiao, Hong-Wei
Abstract: Pulsed pressure (each cycle: 301 kPa pressure time of 10 min and atmospheric pressure relaxation time of 10 min), constant high pressure (301 kPa), and constant atmospheric pressure (101 kPa) pickling were carried out for 48 h to evaluate their quality formation efficiency of "Laba" garlic processing. The kinetics of acetic acid transfer, color parameters ( L ⁎, a ⁎, b ⁎ ) and thiosulfinates content, as well as the hardness change of garlic were investigated. Additionally, the surface microstructure and ultrastructure of raw and pickled garlics were observed using confocal laser scanning microscopy (CLSM) and transmission electron microscopy (TEM), respectively. Results indicated that the pulsed pressure pickling effectively enhanced acetic acid transfer (from 0.32% to 0.65%), degradation of thiosulfinates (from 5.18 mg/mL to 1.72 mg/mL), changes in color ( L ⁎ : from 81.53 to 38.61, a ⁎ : from −1.66 to −19.75, b ⁎ : from 21.03 to 2.23), and hardness (from 19, 249.87 g to 12, 116.40 g) of garlic cloves in 48 h. Garlic cloves turned green initially at the bottom stem node plateau and the top part and then the changes gradually spread to the hollow middle section. Compared with the intact fresh garlic cells, the cell membranes and cell walls of the pickled garlic were severely altered under pulsed pressure pickling process, while the typical plasmolysis was observed under atmospheric pressure. The findings indicate that the pulsed pressure pickling can extensively shorten the processing time due to effective mass transfer of acetic acid and at the same time enhances the final products quality. Industrial relevance: "Laba" garlic is a popular Chinese pickling snacks due to its desired green color and acid taste as well as its health promoting functions. At present, natural pickling under constant atmospheric pressure is still the main method of producing "Laba" garlic. However, the low mass transfer and poor quality change during the pickling process hinder the industrial production of "Laba" garlic pickles. The findings in this study reveal that the pulsed pressure pickling of "Laba" garlic can be a promising pickling method compared to the commonly used pickling methods due to its high processing efficiency. This study also provides insightful information for developing industrial "Laba" garlic pickling process. Highlights: Pulsed pressure pickling enhances acetic acid mass transfer and quality formation of "Laba" garlic. Color turns green initially at the bottom and top part and then spreads to the hollow middle section. Cell membranes and cell walls of garlic were severely altered under pulsed pressure pickling process. Pulsed pressure pickling is a promising method for "Laba" garlic processing.